2003
DOI: 10.1366/000370203322102780
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Enhanced Ionization with Avalanche Amplification: Detection of Cesium at fg/mL Levels

Abstract: The avalanche amplification of the laser-enhanced ionization signal of Cs atoms in a flame has been studied. Ionization of Cs atoms, enhanced by two-step excitation, was detected in hydrogen and propane flames. By employing the effect of avalanche amplification of electrons, high signal-to-noise ratio (approximately 10(4)) was obtained for a 100 ppt Cs solution. The extrapolated limit of detection was 30 fg/mL (ppq).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The selection of the pumping scheme, the energy of the exciting tunable laser and the spatial arrangement between a laser beam and electrode enable the achievement of an extremely low limit of detection down to 30 fg ml À1 . 10 At the same time, the linear dynamic range for lithium determination reaches 7 or more orders of magnitude with the use of this two-step excitation scheme. 11 Another advantage of lithium determination by LEI is the negligible inuence of sodium on the analytical results.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The selection of the pumping scheme, the energy of the exciting tunable laser and the spatial arrangement between a laser beam and electrode enable the achievement of an extremely low limit of detection down to 30 fg ml À1 . 10 At the same time, the linear dynamic range for lithium determination reaches 7 or more orders of magnitude with the use of this two-step excitation scheme. 11 Another advantage of lithium determination by LEI is the negligible inuence of sodium on the analytical results.…”
Section: Introductionmentioning
confidence: 82%
“…The optical emission from a $100 mm central region of the laser plume was collected by a monochromator equipped with a time-gated PMT (9). A capacitive microphone (10) placed at a distance of 10 cm from the ablated target recorded the acoustic signal. An avalanche photodiode (11) and a square wave generator (12) were used to synchronize the ablation and pump lasers.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Further increase in sensitivity can be achieved with avalanche ionisation, i.e., with the 10 3 ± 10 5 -fold multiplied current of the primary electron ± ion pairs. 213,214 Application of nanosecond lasers and nanosecond-resolution registration electronics in some cases enables separating the fast response due to the parasitic molecular ionisation from the slower collisional ionisation response in LEIS at reduced pressures. 215 The parasitic ionisation can also be minimised by shielding the flame from air with an outer concentric argon flow.…”
Section: Atomic Ionisation Spectrometrymentioning
confidence: 99%
“…When analyte excitation proceeds through strong optical transitions and with adequate laser pulse energy, the ionization process becomes extremely efficient and, given a charge collection efficiency near unity, practical limits of detection (LOD) in the pg/mL range are obtainable for many elements, and can be as low as a few tens of fg/mL. 3 This extremely high detection sensitivity makes LEI well suited for microanalysis at the trace level, as was reported by Riter et al in their work on the analysis of blood microsamples by graphite furnace LEI 4 and, more recently, by Gravel et al, who reported on the development of a very sensitive technique based on the combination of laser ablation and laser-enhanced ionization (LA-LEI) for the trace analysis of solid samples. 5 The use of an argon-sheathed concentric argon/oxygen/acetylene flame was shown to greatly enhance LEI sensitivity while eliminating spectral interference from the two-photon ionization of nitric oxide, thus providing higher sensitivity and signal-to-noise ratios.…”
Section: Introductionmentioning
confidence: 99%